IMPLEMENTASI MAQASHID SYARIAH PADA ZAKAT PRODUKTIF DI BAZNAS DKI JAKARTA DAN LAZ DOMPET DHUAFA - Lutfi, Mohammad (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2023)
The aim of this research is to find out the embodiment of Maqashid Syariah in Productive Zakat at BAZNAS DKI Jakarta and LAZ Dompet Dhuafa. Maqashid Syari'ah perspective (objectives and purposes of sharia), obliging productive zakat is valid and appropriate. Because it is more in line with the objectives of the zakat law, which is basically taken from the rich and given to the poor, this is the basic reason why productive zakat is required because it is in accordance with maqaid syari'ah and also to create a sense of justice in society. The provision of productive zakat is carried out by providing guidance and assistance to mustahik so that their business activities can run smoothly besides that BAZNAS DKI Jakarta and LAZ Dompet Dhuafa must also provide spiritual and intellectual religious guidance so that the quality of faith and Islam of mustahik increases.